Економічна безпека як запорука економічної ефективності будівельного підприємства - Федосова, О. В.; Молодід, О. О. (Ways to Improve Construction Efficiency, 2012)
Investigational and it is well-proven that a technological constituent comes forward the dominant functional constituent of economic security of a build enterprise, and it is submitted it technical, resource-material and skilled. The algorithm of development of complex of tekhno-ekonometrichnikh dependences by which it is possible to define a level and state of economic security of a build enterprise is offered.